2018
DOI: 10.1186/s12199-018-0753-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between time-related work factors and dietary behaviors: results from the Japan Environment and Children’s Study (JECS)

Abstract: Background: Few studies have examined the association of workhours and shift work (referred to here as "time-related work factors") with dietary behaviors. We aimed to investigate this association, as well as the dietary behaviors among individuals with occupations characterized by time-related work factors. Methods:A cross-sectional study was performed using data from the Japan Environment and Children's Study. The study included 39,315 working men. Dietary behaviors (i.e., skipping breakfast, eating out, eat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 19 publications
1
16
0
1
Order By: Relevance
“…Our results show that manual workers from sectors such as agriculture, manufacturing and construction had a lower consumption of fruit compared to non-manual workers such as engineers and mid-level technicians and administrators, where consumption was greater. Earlier studies consistently support this finding and confirm that manual workers consume less fruit and vegetables compared to all other occupational categories [ 9 , 33 , 36 , 37 ]. The results are similar in terms of vegetables, where a manual profession, such as construction work, has lower consumption, with greater consumption among scientific professionals and engineers.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Our results show that manual workers from sectors such as agriculture, manufacturing and construction had a lower consumption of fruit compared to non-manual workers such as engineers and mid-level technicians and administrators, where consumption was greater. Earlier studies consistently support this finding and confirm that manual workers consume less fruit and vegetables compared to all other occupational categories [ 9 , 33 , 36 , 37 ]. The results are similar in terms of vegetables, where a manual profession, such as construction work, has lower consumption, with greater consumption among scientific professionals and engineers.…”
Section: Discussionsupporting
confidence: 73%
“…One’s occupation also implies exposure to different working conditions which can be associated with poor dietary habits. For example, work-related stress, shift work, occupations with long working hours and frequent changes in the workplace are associated with low consumption of fruit and vegetables [ 8 , 9 ]. Factors that facilitate access to an unhealthy diet in the workplace have been shown to be important [ 10 ], perhaps because the best possible option is often fast food, or because the rhythm of work limits the time available for eating and/or choosing healthy foods [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high mortality rate among service workers in Japan deviates from this pattern, however, a trend that has been observed since the 1980s [13]. One possible explanation relates to the irregular work shifts among service workers [23]. In Japan, the opening hours of service industries such as restaurants, bars, supermarkets, and convenience stores are generally long, and stores that remain open 24 h are fairly common.…”
Section: Discussionmentioning
confidence: 98%
“…The underlying mechanism might be changes in lifestyle factors including dietary pattern, sleep time, and physical activity. Firstly, it has been suggested that long working hours are positively linked to poor dietary behaviours, including skipping breakfast, eating out, eating instant food, overeating, and fast eating . These unhealthy eating habits are recognized as factors in the development of weight gain and obesity .…”
Section: Discussionmentioning
confidence: 99%